THE EFFECT OF ELECTRONIC INSURANCE UPON COMPETITIVE ADVANTAGE: A CASE STUDY IN THE IRAQI INSURANCE COMPANY (World Economics and Finance Bulletin, 2022)
The research aims at verifying the effect of electronic insurance by describing an independent variable represented by dimensions (customer attraction, retention, engagement, identifying customer preferences, communicating with customers) and the competitive advantage as a dependent variable represented by the dimensions (cost, quality, flexibility, and delivery). The research posed a basic question: Is there an impact relationship for the Einsurance variable on the competitive advantage variable?. In order to verify the contents of the answer to the previous question, 109 employees in the Iraqi General Insurance Company were randomly selected. The research adopted the descriptive analytical method, where a questionnaire was prepared by the researcher, which was considered the main tool in data collection. A questionnaire analysis was conducted by depending on the statistical program (SPSS V25) and the supporting program (AMOS V25). The research has come up with several conclusions, namely: there is a positive direct effect of E-insurance on the competitive advantage.